Immunotherapy in Gynaecological Oncology: The Italian Landscape - Luca Pace; Michela Villa; Roberta Massobrio; Margherita Giorgi; Daniela Attianese; Annamaria Ferrero (IMR Press, 2023)
Objective: The potential of immunotherapy in gynaecological malignancies is being investigated in recent years. This review will discuss the current status of immunotherapy in endometrial (EC), ovarian (OC) and cervical (CC) cancers with particular attention to the Italian reality. Mechanism: The websites of Multicenter Italian Trials in Ovarian cancer (MITO) and Mario Negri Gynecologic Oncology (MaNGO) groups were consulted and an in-depth search was carried out on clinicaltrials.gov. Trials started from 2014 to September 2022 were included in the search. Monoclonal antibodies, immune checkpoint inhibitors and drug-conjugated antibodies (ADCs) therapies were considered. Findings in Brief: The studies with the greatest clinical impact, specifically in terms of PFS (Progression Free Survival) and adverse events reported, and with the widest participation of Italian centers have been presented. In EC the impact of immunotherapy has been considerable, as demonstrated by the inclusion of immunotherapy in today's treatment pathways. The identification of new biomarkers will make it possible to select patients who can best benefit from this type of therapy. Immunotherapy in OC has been a complex challenge for years, as early trials have shown. The results of further trials are now expected. CC seems to be one of the most interesting settings for immunotherapy and some results are already in the clinical management of advanced disease. Conclusions: Several trials have led to the approval of new drugs by regulatory agencies in gynaecological oncology, making immunotherapy not only an important promise for the future but also a concrete current reality for thousands of women worldwide.